1997
DOI: 10.2514/2.2205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computational Aeroacoustic Prediction Methods for Transonic Rotor Noise

Abstract: This paper compares two methods for predicting transonic rotor noise for helicopters in hover and forward ight. Both methods rely on a computational uid dynamics (CFD) solution as input to predict the acoustic near and far elds. For this work, the same full-potential rotor code has been used to compute the CFD solution for both acoustic methods. The rst method employs the acoustic analogy as embodied in the Ffowcs Williams{Hawkings (FW{H ) equation, including the quadrupole term. The second method uses a rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…A recent numerical comparison by Brentner et al 5 of the helicopter rotor noise prediction code WOPWOP+, 6{8 which uses a FW{H based formulation including an approximate quadrupole calculation, with a rotating Kirchho code RKIR 9,10 has shown that both methods can predict the rotor noise equally well. In that work, however, neither method was demonstrated to be clearly superior.…”
Section: Introductionmentioning
confidence: 99%
“…A recent numerical comparison by Brentner et al 5 of the helicopter rotor noise prediction code WOPWOP+, 6{8 which uses a FW{H based formulation including an approximate quadrupole calculation, with a rotating Kirchho code RKIR 9,10 has shown that both methods can predict the rotor noise equally well. In that work, however, neither method was demonstrated to be clearly superior.…”
Section: Introductionmentioning
confidence: 99%
“…The underprediction of the negative peak is a result of using a coarse grid. Brentner et al 5 found that the agreement is improved with a ner grid. Small oscillations in the signal, near the two positive peaks, are evident in both the Kirchho and FW{H solutions.…”
Section: Numerical Comparison Of Formulationsmentioning
confidence: 98%
“…Now that the FW{H/RKIR code has been introduced, we wish to examine the sensitivity of each formulation to the placement of the integration surface. Brentner et al 5 found that the Kirchho solution varied somewhat with location of the integration surface. Figure 2 shows a cross section of ve dierent integration (Kirchho) surface locations ranging from one grid line o the surface to 1.37 chordlengths o the surface.…”
Section: Numerical Comparison Of Formulationsmentioning
confidence: 99%
“…This equation is often used as the key tool for the prediction of noise produced by rotating propeller blades, including helicopter rotors and fans. In a number of further works [14,20, 98}100] modi"ed versions of that equation as well as the relevant computational codes were suggested, including those applied for sonic and supersonic surface motions in order to avoid some singularities. It should be noted that no consistent theoretical concept of sound generation has been o!ered speci"cally for transonic and supersonic #ows, and so if approach [45] is applied to such #ows, then new di$cult questions arise in addition to those discussed above.…”
Section: On Some Other Approaches To the Theory Of Aerodynamic Soundmentioning
confidence: 99%
“…After applying a decomposition procedure like that de"ned by equation (14) one must forget the old variable Z, and only new variables Z K "+Z KH , and Z C "+Z CH , are to be used. Then equation (15) should be rewritten as…”
Section: Then the Functionsmentioning
confidence: 99%